Reversed halo sign caused by huge tricuspid native valve infective endocarditis associated with community-acquired methicillin-resistant Staphylococcus aureus. Issue 1 (February 2015) - Saraya, Takeshi; Kikuchi, Ken; Araki, Koji; Uehara, Yuki; Makino, Hiroshi; Tamura, Masaki; Hirukawa, Ichiro; Honda, Kojiro; Yokoyama, Takuma; Kurai, Daisuke; Ishii, Haruyuki; Fujiwara, Masachika; et al.
Abstract : Introduction: A reversed halo sign (RHS) has diverse differential diagnoses such as cryptogenic organizing pneumonia, fungal, bacterial and mycobacterial infections, and systemic and neoplastic diseases. However, no report has been described regarding an RHS associated with infective endocarditis (IE). Case presentation: A 43‐year‐old man was transferred to our hospital because of persistent pyrexia, chest pain with multiple cavitary lung lesions for a month. He was diagnosed with tricuspid native valve IE caused by massive vegetations in the context of CA‐MRSA (staphylococcal cassette chromosome mec type II, sequence type 91, clonal complex 509) infection with multiple pulmonary septic emboli, manifesting as an atypical RHS. Conclusion: The present case showed huge tricuspid native valve IE associated with community‐acquired meticillin‐resistant Staphylococcus aureus (CA‐MRSA), which was analysed successfully by multilocus sequence typing.